First detection of Mnemiopsis leidyi (Ctenophora, Bolinopsidae) in Sardinia (S’Ena Arrubia Lagoon, Western Mediterranean): a threat for local fishery and species recruitment - DICIOTTI, R.; CULURGIONI, J.; SERRA, S.; TRENTADUE, M.; CHESSA, G.; SATTA, C. T.; CADDEO, T.; LUGLIE, A.; SECHI, N.; FOIS, N. (Mediterranean Marine Science, 2016)
The invasive comb jelly Mnemiopsis leidyi is a lobate ctenophore native of coastal and estuarine waters of the temperate western Atlantic Ocean. In the last decades this species has expanded its range of distribution, colonizing marine and transitional environments in Europe. In October 2015, during a survey fishing the European eel Anguilla anguilla in Sardinia (western Mediterranean), a massive bloom of this specie was observed in the eutrophic S’Ena Arrubia Lagoon for the first time. In November 2015, sampling was conducted at three stations in the lagoon and in a fyke net, in order to estimate the abundance of M. leidyi and to determine its impact on the fishing activity. The results showed an abundance of 2.83 ctenophores m-3. Specimens were all adults, measuring 18 - 62 mm total length. The abundant number of ctenophores (6837 individuals per fyke net) damaged fishing operations, reducing catches and affecting the performance of fishing gears. Since there is no effective mechanical, chemical or biological method to counter M. leidyi, the short term economic damage may be approached by new management measures of fisheries. In addition, other actions against the recurring of M. leidyi invasion, can include management strategies, in particular those finalized to reduce the high trophic state of the lagoon.